PERTANGGUNGJAWABAN PENGGUNAAN ALOKASI DANA DESA PADA PEMERINTAHAN DESA DI KABUPATEN DONGGALA - Husin Sulumin, Hasman (Katalogis, 2015)
The Objective of this research was to knowledge mechanism responsibility village regencyÂ inside to use allocation donation village and supervision inside to use allocation donation village because of responsibility regency. Based on the data analysis result, it can be concluded that the mechanism responsibility vilage regency inside to use Allocation Donation Village begin from planning, implementation, supervision end as responsibility employing allocation donation village at village regency in Donggala regency already materialize law operate regency, which institution manage to already understand the arrangement manage the finances of state which the responsibility. Supervision inside to use allocation donation village begin regency already in a ladder from intern efficient village because of the Discussion Village, Subdistrict Head, Secretariat area village regency, Departement Accession Ricties and Assets Area end Inspetorate regency in demand pass through supervison affix the refer at the arrage legistation which prevailk